"Analyze of inflation and economic growth relationship in Burundi" - Jean Tony Ezako (Cogent Economics & Finance, 2023)
The objective of this paper was to analyse the relationship between inflation and economic growth in Burundi and to determine whether there is an inflation threshold or not to allow monetary authority to adopt the optimal policies to deal with shocks. With annual data from 1990 to 2020, the ARDL approach is adopted to assess the short and long run relationship between inflation and economic growth. The results showed a negative and significant relationship in the short run between inflation and economic growth, and a positive and significant relationship between investment, household consumption, and exchange rate with economic growth in the long run. Moreover, with the conditional least square (CLS) method used to determine the threshold, an inflation threshold of 13% above which inflation is harmful to growth by 3.7% was found. In addition, two stage least square (2SLS) was used for robustness checking and yielded the same results. We recommend to policy makers to target an inflation ceiling of 13%, to coordinate the various policies, whether monetary, budgetary and fiscal, and to promote investment and improve the structure of production.
Keywords: C01; C24; E31; E5; 330; inflation; Inflation threshold; monetary policy; relationship inflation economic growth